2017
DOI: 10.1176/appi.ps.201600233
|View full text |Cite
|
Sign up to set email alerts
|

Diversion of Veterans With Criminal Justice Involvement to Treatment Courts: Participant Characteristics and Outcomes

Abstract: Objective This study compared characteristics and outcomes between veterans who participated in veterans treatment courts (VTCs) and veterans involved in criminal justice who participated in other treatment courts (TCs) or who participated in neither VTCs or TCs. Methods Data from 22,708 veterans (N=8,083 VTC participants, 680 participants in other TCs [other-TC participants], and 13,945 participants in neither VTCs nor TCs [non-TC participants]) in the Veterans Justice Outreach (VJO) program were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Several articles focused on conditions and experiences related to military service such as PTSD and trauma (Backhaus et al, 2016; Bennett, Morris, Sexton, Bonar, & Chermack, 2018; Elbogen et al, 2012; Saxon et al, 2001; Sigafoos, 1994). A number of observational studies addressed violence (Elbogen et al, 2012; Hoyt et al, 2014; MacManus et al, 2013) and Veterans Treatment Courts (Clark, Blue-Howells, & McGuire, 2014; Knudsen & Wingenfeld, 2016; Tsai, Flatley, Kasprow, Clark, & Finlay, 2017). Only one study we identified examined suicide as the primary outcome (Ilgen, Harris, Moos, & Tiet, 2007), though another study addressed suicide along with other factors (Kimbrel et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Several articles focused on conditions and experiences related to military service such as PTSD and trauma (Backhaus et al, 2016; Bennett, Morris, Sexton, Bonar, & Chermack, 2018; Elbogen et al, 2012; Saxon et al, 2001; Sigafoos, 1994). A number of observational studies addressed violence (Elbogen et al, 2012; Hoyt et al, 2014; MacManus et al, 2013) and Veterans Treatment Courts (Clark, Blue-Howells, & McGuire, 2014; Knudsen & Wingenfeld, 2016; Tsai, Flatley, Kasprow, Clark, & Finlay, 2017). Only one study we identified examined suicide as the primary outcome (Ilgen, Harris, Moos, & Tiet, 2007), though another study addressed suicide along with other factors (Kimbrel et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Since many of the participants in VTCs are not necessarily individuals with service‐related needs (Tsai et al ), looking at stated explanations for the creation and administration of justice in VTCs can leave an incomplete picture of their purpose and practice. Further, cross‐national quantitative data show variation in court rules and procedures that make it hard to generalize the relationship between purpose and practice without qualitative analysis (Flatley et Al.…”
Section: Studying a Vtc In Practicementioning
confidence: 99%
“…Although the sample sizes involved in both examples were small, these results appear promising. Tsai et al (2016) evaluated national data from the VJO program, noting positive outcomes related to independent housing and employment for VTC participants.…”
Section: Early Datamentioning
confidence: 78%
“…If one of the primary ethical justifications favoring VTCs is their humanitarian purpose, another outcome of interest is whether participation in the VTC ultimately leads to improvement in the veterans' quality of life and psychiatric symptoms. The improved employment and independent housing outcomes (Tsai et al, 2016) are augmented by a pilot study of 86 veterans in an Ohio VTC program that found highly significant improvements in PTSD symptoms, depression symptoms, substance use and recovery orientation, sleep quality, social connectedness, and emotional wellbeing. Specific components of the court program that were found to be particularly effective were trauma-focused treatment, peer mentorship, and medication therapy (Knudsen & Wingenfeld, 2016).…”
Section: Early Datamentioning
confidence: 99%